2021
DOI: 10.1002/jbt.22893
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin regulates mRNA expression of VEGF‐c, Ang‐1/Tie2, TGF‐β and Smad2/3 to inhibit wound healing in streptozotocin‐induced diabetic foot ulcer rats

Abstract: Diabetic foot ulcer (DFU) is biggest life threats globally and increases their severity increases health complications for health of patients. The present study was investigated to recover the wound healing activity of baicalin in STZ-induced DFU rats by evaluating biochemical and molecular markers. The experimental animals induced with diabetes and excision wounds were treated with different doses of baicalin (25, 50, and 100 mg/kg).The serum glucose level, body weight and food intake were measured. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…During the inflammatory phase, fibroblasts migrate to the wound site, and various growth factors such as TGF-β1 and Ang-1 are released from keratinocytes [71]. Ang-1 and TGF-β are also needed, as they regulate the production of collagen and ensure the availability of hydroxyproline [78]. FLX is known to induce TGF-β1 synthesis and release in vitro in glial cells [79] as well as in humans [80], but no studies have been conducted in experimental models of wound healing yet.…”
Section: Discussionmentioning
confidence: 99%
“…During the inflammatory phase, fibroblasts migrate to the wound site, and various growth factors such as TGF-β1 and Ang-1 are released from keratinocytes [71]. Ang-1 and TGF-β are also needed, as they regulate the production of collagen and ensure the availability of hydroxyproline [78]. FLX is known to induce TGF-β1 synthesis and release in vitro in glial cells [79] as well as in humans [80], but no studies have been conducted in experimental models of wound healing yet.…”
Section: Discussionmentioning
confidence: 99%
“…Baicalin exhibits various pharmacological activities, including anti-inflammatory, antioxidant, and anti-allergic therapies. Previous studies have demonstrated that baicalin protects against pressure stress such as that found in type-2 diabetes and cerebral ischemia injury [23][24][25][26]. Our study suggests that baicalin can reduce advanced-stage pressure ulcers by promoting wound healing related to anti-inflammatory activity.…”
Section: Discussionsupporting
confidence: 60%
“…Diabetic food ulcer is another complication of T1DM, the pathogenesis of which is proven to be correlated with elevated NO, MDA, p-ERK and p-HSP27 while decreased level of SOD, GSH, VEGF-c, Ang-1, Tie-2, TGF-β and Smad2/3. BAI administration reversed all the alterations and eventually promote the wound healing of food ulcer (Mao et al, 2021).…”
Section: Endocrine Glandsmentioning
confidence: 92%